VALIDITY DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE SPECIALISTS OF THE UNIVERSITY OF TECHNICAL DIRECTION - Dilshod Azamatovich Eshnazarov (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Modernity is recognized as the main factor ensuring the development of education in the world, and the quality of education in educational institutions is of particular importance.Socio-economic, scientific and technical changes on a global scale presuppose the organization and management of the training system for future specialists on the basis of a modular approach and the development of the professional competence of future specialists in the Higher Education Institutions. At present, in the educational standards of developed countries, special attention is paid to the formation of global skills of students. Of great importance in this is the modernization of the content of existing education, image-building technologies, a system for assessing the results of assimilation on the basis of modular technology.On the basis of international pedagogical experience, an important place in the implementation of new pedagogical projects, the widespread implementation of innovative achievements in practice and raising the quality of education to a new level is occupied by the preparation of future specialists for professional activities.The article is devoted to the disclosure of the content of the development of professional competence of future specialists in the technical direction of VUZa, through the development of new paradigms of teaching the effective use of the didactic capabilities of information and communication technologies